“As coisa lá da minha mudernage”: entre-lugar, modernidade e sertão na obra artística de Elomar Figueira Mello - Oliveira, Helder Canal de (2014)
The work of Elomar Figueira Mello emerged in the late 1960s. The topics of his songs and poems focus on the appreciation of the backwoods and country culture. He does this contrasting ethos and vision of traditional and modern world. By making this contrast, the artist notes that the interior is modern branded by a hegemonic discourse of late, wilderness, barbarian, among others. Thus, this modern discourse rejects and silences other discourses-explanatory that are not within their assumptions as the philosophical, theological and popular. According to Boaventura de Sousa Santos (2010), this silencing can be designated as epistemicide. Thus, the musician denounces in his art this process of modernization and epistemício engendered by modernity. However, while Elomar makes this complaint he cannot stray of modern rationality, because he keeps the Cartesian dualism as he keeps, for example, a separation between town and country, featuring the first as the site of inhumanity, the prevalence of demonic precepts and the second as the place of redemption, the encounter with God. Moreover, despite the musician in his speech reject modernity, it is possible to observe several modern influences in his life and work as a Protestant orientation and his taste for opera. That is why we think that the work of Elomar Figueira Mello can be characterized as being in a cultural border, in a place in-between.